2021
DOI: 10.1088/1757-899x/1057/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Turning Parameters during Machining of AA6061 composite using RSM Box-Behnken Design

Abstract: CNC machines are currently dominating the machining manufacturing industries. Machining parameters that assume a significant job are shaft speed, feed rate and depth of cut in choosing quality machining. Point of present examination is to locate the ideal turning parameters, and its impact on response during machining of aluminium alloy 6061 with carbide embeds tool. Three process parameters have been adopted to obtain maximum material removal rate and better surface finish using response surface methodology R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Singh et al [13] focused on the reducing the usage of cutting fluids, an effort has been made to present an overview of the various cutting fluid types, cooling techniques, and important alternatives, such as dry machining, cryogenic cooling, minimal amount lubrication, and hybrid cooling. Kumar et al [14] investigated the RSM Box-Behnken Design, modelling and optimisation of turning parameters during machining of AA6061 composite. They also found that feed had the most influence on surface roughness, whereas depth of cut has a big impact on material removal.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [13] focused on the reducing the usage of cutting fluids, an effort has been made to present an overview of the various cutting fluid types, cooling techniques, and important alternatives, such as dry machining, cryogenic cooling, minimal amount lubrication, and hybrid cooling. Kumar et al [14] investigated the RSM Box-Behnken Design, modelling and optimisation of turning parameters during machining of AA6061 composite. They also found that feed had the most influence on surface roughness, whereas depth of cut has a big impact on material removal.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology is used to reduce MRR and surface smoothness. The author found that the multiple responses desirability strategy improved the result [ 11 ]. Taguchi’s L27 orthogonal array technique investigates Al-15%–SiCp metal matrix composite.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the author in [ 11 ] optimized surface quality using the RSM and DFA of aluminum alloys. The RSM and DFA were also used to maximize aluminum alloy energy utilization, surface waviness, and material removal rate (MRR) by taking the cutting depth, the rate of feed, and the cutting speed into account [ 1 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%